2016
DOI: 10.18006/2016.4(2).133.141
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicines among residents in upland cavite, Philippines: their knowledge, patterns of use and attitudes

Abstract: The study was aimed to determining the knowledge, patterns of use, and attitude towards the use of complementary and alternative medicines (CAM) by herbalists (n=38) and lay people (n=582) from the municipalities of Indang, Maragondon, Amadeo, Magallanes, and Alfonso and the city of Tagaytay, all located in the upland portion of the province of Cavite. Data pertinent to the afore-said aims were gathered through questionnaires and focus group discussions. Nine forms of CAM were documented as used by the intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…These findings of ours are consistent with the other findings, which reported herbal medicines/natural products as most commonly used CAM. [ 24 30 ] Although CAM usage pattern varies among countries and population, majority of studies reported herbal and natural products were most commonly used. [ 6 ] This could be due to easy availability and accessibility of herbal medicines and dietary supplements and consumers often presume them as safe over conventional medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings of ours are consistent with the other findings, which reported herbal medicines/natural products as most commonly used CAM. [ 24 30 ] Although CAM usage pattern varies among countries and population, majority of studies reported herbal and natural products were most commonly used. [ 6 ] This could be due to easy availability and accessibility of herbal medicines and dietary supplements and consumers often presume them as safe over conventional medicines.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 17 ] Vast numbers of studies from different parts of the world have made an attempt to evaluate the knowledge, attitude, and practice of health-care students toward CAM usage and a considerable number of studies addresses the CAM usage pattern among general public and patients. [ 5 18 19 20 21 22 23 24 ] The data from these studies reveal that there is a wide variation in the knowledge, attitude, and practice of medical professionals, patients, and general public toward CAM usage.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional medicine or complementary and alternative medicine (CAM) continues to increase its use globally (Horneber et al, 2012;World Health Organization, 2019). This treatment method is found in almost every country, such as in continental Europe (Eardley et al, 2012;Eurocam, 2014;Kemppainen et al, 2018), Australia (Xue et al, 2007), America (Roth and Kobayashi, 2008) ; NCCAM, 2013) and Asia (Khan and Sajid, 2014;Pengpid, 2015, 2018;Ching, Flores and Acelajado, 2016;Farooqui et al, 2016;Mastura et al, 2017;Reihaneh, Ramezani & Ramezani, 2017) with a tendency to use more and more from year to year. Worldwide, traditional and complementary medicine is one of the mainstays in health services (World Health Organization, 2013).…”
Section: Introductionmentioning
confidence: 99%